Design modification of high speed diesel engine to accomodate compressed natural gas - Yusaf, Talal F.; Shamsuddin, Abdul Halim; Ali, Yusoff; Ismail, Ahmad Faris (Asian Institute of Technology RERIC, 1996)
Compressed naturai gas CNG was inducted through various experimental mixers mounted between the air manifold and air filter of a high speed four stroke diesel engine. Pilot diesel was used for the initial ignition. An experimental plate was inserted between the cylinder face and the engine block to reduce the compression ratio from 22.9: 1 to 16: 1. The power, torque, lubricant oil temperatures, coolant water temperatures, and exhaust gas temperatures of the modified engine are evaluated. The results were compared with the data of diesel fuel. An eddy current dynamometer and group of temperature sensors have been used to evaluate the performance of the engine.